Regulation of PEST-containing nuclear proteins in cancer cells: implications for cancer biology and therapy - Jiang, Kai-Chun; Zhu, Yong-Hao; Jiang, Zhi-Liang; Liu, Yi; Hussain, Wahab; Luo, Huang-Yin; Sun, Wei-Hang; Ji, Xin-Ying; Li, Ding-Xi (Frontiers in Oncology, 2025)
The PEST-containing nuclear protein (PCNP) is a nuclear protein involved in the regulation of cell cycle progression, protein degradation, and tumorigenesis. PCNP contains a PEST sequence, a polypeptide structural motif rich in proline (P), glutamic acid (E), serine (S), and threonine (T), which serves as a proteolytic recognition signal. The degradation of specific proteins via the PEST sequence plays a crucial role in modulating signaling pathways that control cell growth, differentiation, apoptosis, and stress responses. PCNP is primarily degraded through the ubiquitin-proteasome system (UPS) and the calpain pathway, with phosphorylation of threonine and serine residues further accelerating its degradation. The ubiquitination of PCNP by the ring finger protein NIRF in an E3 ligase-dependent manner is well documented, along with its involvement in the MAPK and PI3K/AKT/mTOR signaling pathways. Additionally, PCNP is implicated in p53-mediated cell cycle arrest and apoptosis, which are essential for inhibiting tumor growth. To explore the role of PCNP in cancer, this review examines its effects on cell growth, differentiation, proliferation, and apoptosis in lung adenocarcinoma, thyroid cancer, ovarian cancer, and other malignancies derived from glandular epithelial cells. By focusing on PCNP and its regulatory mechanisms, this study provides a scientific basis for further research on the biological functions of the PEST sequence in tumor development and cancer progression.